Environmental impacts of macroeconomic and sectoral policies (The World Bank, 1998)
The papers in this volume are particularly useful since they come at a time when the environmental impacts of macroeconomic policies have come under close scrutiny. They look at the ecological and social impacts of structural adjustment programs and other macroeconomic policies in an integrated way.